Search for massive resonances decaying into WW, WZ or ZZ bosons in proton-proton collisions at s?=13s=13 TeV - Sirunyan, A. M.; Tumasyan, A.; Adam, W.; Asilar, E.; Bergauer, T.; Brandstetter, J.; Brondolin, E.; Dragicevic, M.; Ero, J.; Flechl, M.; Friedl, M.; Fruhwirth, R.; et al. (My University, 2017)
A search is presented for new massive resonances decaying to WW, WZ or ZZ bosons in l upsilon q (q) over bar and q (q) over barq (q) over bar final states. Results are based on data corresponding to an integrated luminosity of 2.3-2.7 fb(-1) recorded in proton-proton collisions at root s = 13TeV with the CMS detector at the LHC. Decays of spin-1 and spin-2 resonances into two vector bosons are sought in the mass range 0.6-4.0TeV. No significant excess over the standard model background is observed. Combining the results of the l upsilon q (q) over bar and q (q) over barq (q) over bar final states, cross section and mass exclusion limits are set for models that predict heavy spin-1 and spin-2 resonances. This is the first search for a narrow-width spin-2 resonance at root s = 13TeV.
Citation: Sirunyan, A. M., Tumasyan, A., Adam, W., Asilar, E., Bergauer, T., Brandstetter, J., . . . Collaboration, C. M. S. (2017). Search for massive resonances decaying in to WW,WZ or ZZ bosons in proton-proton collisions at root s=13 TeV. Journal of High Energy Physics(3), 56. doi:10.1007/jhep03(2017)162
Keywords: Beyond Standard Model; Hadron-Hadron Scattering (Experiments); Particle; And Resonance Production; Proton-Proton Scattering; Hadron-Collisions